Segmentation Base Advance Approach for Detect and Classify Leaf Diseases: A Novel Approach for Leaf Disease Detection and Classification (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The most challenging process in agricultural application is id identification of leaf individually. In this paper, the classification of leaf diseases is proposed along with the leaf identification of leaf identification, initially, the leaf skeletons are identified based on grapes image. Since, the leaf skeletons are used for estimating the positions and directions of the leaves. Using advance segmentation algorithm is proposed for retrieval of skeletons and identify diseases. If diseases will detected that using machine learning approach for classify types of diseases work on other result analysis parameters for classify type.